Cover Picture: Structural Determinants of the Selectivity of 3‐Benzyluracil‐1‐acetic Acids toward Human Enzymes Aldose Reductase and AKR1B10 (ChemMedChem 12/2015). Issue 12 (December 2015) - Ruiz, Francesc X.; Cousido‐Siah, Alexandra; Porté, Sergio; Domínguez, Marta; Crespo, Isidro; Rechlin, Chris; Mitschler, André; de Lera, Ángel R.; Martín, María Jesús; de la Fuente, Jesús Ángel; Klebe, Gerhard; Parés, Xavier; et al.
Abstract : The front cover picture shows how to achieve selective inhibition of two closely related human enzymes, with different biological activities, using a common scaffold. By switching from a chloro‐3‐nitrobenzyl [in compound3, 2‐(3‐(4‐chloro‐3‐nitrobenzyl)‐2, 4‐dioxo‐3, 4‐dihydropyrimidin‐1(2 H )‐yl)acetic acid] to a tetrabromo‐6‐methoxybenzyl decorated scaffold [in compound4, 2‐(2, 4‐dioxo‐3‐(2, 3, 4, 5‐tetrabromo‐6‐methoxybenzyl)‐3, 4‐dihydropyrimidin‐1(2 H )‐yl)acetic acid], the potency and selectivity profile shifts from aldose reductase (AR) to AKR1B10. The underlying rationale can be grasped from the crystal structures and thermodynamic profiles of AR with3 and AKR1B10 with4, which is graphically depicted by the popular saying "kill two birds with one stone". This selectivity is also maintained in cellular studies, anticipating an efficient drug design and development towards diabetes, cancer, and inflammation. More details can be found in the Full Paper by Francesc X. Ruiz, Alberto Podjarny et al. onpage 1989 in Issue 12, 2015 (DOI:10.1002/cmdc.201500393 ).